2013
DOI: 10.1007/s10900-012-9644-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Women Lost to Follow-Up in Cardiovascular Community Health Interventions: Findings from the Sister to Sister Campaign

Abstract: Community-based interventions (CBI) have been targeted as a potential means of tackling cardiovascular disease in women. However, there have been mixed results in terms of their impact on health, with at least some of this being attributed to high attrition rates. This study explores factors that may be contributing to the low retention of women in cardiovascular CBIs. In 2009, Sister to Sister, a national organization that sponsors community health fairs, provided free cardiovascular health screenings for a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 11 publications
2
6
1
Order By: Relevance
“…Our age, smoking, and depression findings corroborate previous work in cardiovascular cohorts [9][10][11], suggesting that study completion may occur systematically depending on these patient characteristics. Younger individuals may feel less vulnerable to disease or less benefit from long-term involvement in research studies [10].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our age, smoking, and depression findings corroborate previous work in cardiovascular cohorts [9][10][11], suggesting that study completion may occur systematically depending on these patient characteristics. Younger individuals may feel less vulnerable to disease or less benefit from long-term involvement in research studies [10].…”
Section: Discussionsupporting
confidence: 89%
“…Based on previous research [7][8][9][10][11], several characteristics were identified as potential factors associated with study completion. Medication use at time of hospitalization (i.e., Calcium antagonists, ACE inhibitors, and statins), number of medications at time of discharge, previous diagnosis of dyslipidemia, hypertension, and diabetes were determined from chart review.…”
Section: Potential Factors Associated With Study Completionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only increasing age and cognitive impairment seem to be independently associated with not completing longitudinal studies [8]. Moreover, few studies have examined whether completers and dropouts differ systematically in cohorts of cardiovascular patients or cardiovascular prevention [911]. In these studies, study completion was associated with several sociodemographic (i.e., higher income, lower body mass index (BMI), older age, female sex, and white ethnicity), access-to-care (i.e., attendance of health fairs and having health insurance), clinical (i.e., not smoking, having metabolic syndrome and hypertension, lower HDL cholesterol level, and adherence to cardiac medication), and psychosocial (i.e., lower levels of depression, anxiety, and general stress) characteristics [911].…”
Section: Introductionmentioning
confidence: 99%
“…These studies, however, had important limitations. For instance, one study only reported unadjusted results [9] whereas another did not examine men or report their female participants’ age [11]. Moreover, the two studies that did report age [9, 10] only examined older adults (i.e., greater than 59 years).…”
Section: Introductionmentioning
confidence: 99%